PERAN STRATEGIS KESULTANAN PERLAK DALAM PROSES ISLAMISASI AWAL DI NUSANTARA - Elsha Putriany Br Girsang; Angel Sinambela; Fikri Maulana Saleh Harefa; Jeremy Arif Gonzales Tarigan; Pristi Suhendro Lukitoyo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research discusses the history of the establishment of the Perlak Sultanate and its contribution to the process of spreading Islam in the Nusantara region. Through qualitative methods and a historical approach, the research findings show that Perlak's strategic position on the Malacca Strait trade route, interaction with Muslim traders, as well as the role of scholars and educational institutions, were the main factors driving the development of Islam in the area. The Perlak Sultanate played a significant role as a center of trade and the spread of Islam, which accelerated the process of Islamization in the Nusantara.